2008
DOI: 10.1016/j.tim.2008.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Control of bovine tuberculosis in British livestock: there is no ‘silver bullet’

Abstract: Bovine tuberculosis (bTB; Mycobacterium bovis) is a bacterial infection of cattle that also affects certain wildlife species. Culling badgers (Meles meles), the principal wildlife host, results in perturbation of the badger population and an increased level of disease in cattle. Therefore, the priority for future management must be to minimize the risk of disease transmission by finding new ways to reduce the contact rate among the host community. At the farm level, targeting those individuals that represent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 59 publications
0
34
0
1
Order By: Relevance
“…This is most likely due to Co. Donegal being the most exposed county, with poor soils and mountainous areas [19]. There have been previous attempts in Britain to use badger abundance metrics to produce risk maps for bTB to cattle herds at national levels [28,42]. Bessell et al [29] used one of these risk maps, the probability of main-sett presence, to model its relationship with cattle herd breakdown risk at a national scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is most likely due to Co. Donegal being the most exposed county, with poor soils and mountainous areas [19]. There have been previous attempts in Britain to use badger abundance metrics to produce risk maps for bTB to cattle herds at national levels [28,42]. Bessell et al [29] used one of these risk maps, the probability of main-sett presence, to model its relationship with cattle herd breakdown risk at a national scale.…”
Section: Discussionmentioning
confidence: 99%
“…We added a variable which represented a metric of badger social group density (derived from the maps within [19]), as a means of controlling for underlying heterogeneity of badger density. This variable represents the suitability of landscapes for social group density based on main sett abundance [28,29]. This metric was scaled to values between zero and one; higher values denote higher densities (see [19] for details).…”
Section: Methodsmentioning
confidence: 99%
“…Failure to account for the complexity of social networks through which diseases may be transmitted may in turn be responsible for the failure of disease control strategies based simply on one-off population reduction [6]. For example, a study of possums Trichosurus vulpecula Kerr in New Zealand showed a non-linear relationship between contact rates and population density [7], clearly in contrast to the traditional assumption of density dependence.…”
Section: Introductionmentioning
confidence: 99%
“…While the RBCT showed that badger culling operations and cattle herd breakdowns rates are strongly and significantly associated with each other [8-10], relatively little is understood about the role of badgers in herd breakdowns across GB, though a recent paper has analysed risk factors for badger presence [11]. These analyses have been extrapolated to produce a prediction of badger distribution in GB, features that have previously been suggested could be used to predict risk of bTB to cattle [12]. …”
Section: Introductionmentioning
confidence: 99%